initial value problem
d2y/dx2-3xdy/dx+2x=0, x0=6 d2y/dx2=-5
(i) Solve the problem using the standard form of the general solution, based on the characteristic
equation.
(ii) Solve the problem as a system of rst order ODEs, by letting y1 = X and y2 = y01

Respuesta :

Since you explicitly mention "characteristic equation", I assume you mean the differential equation is

[tex]\dfrac{d^2y}{dx^2} - 3\dfrac{dy}{dx} + 2y = 0[/tex]

because the phrase is often used in the context of linear ODEs with constant coefficients.

The characteristic equation is then

[tex]r^2 - 3r + 2 = (r - 2) (r - 1) = 0[/tex]

with roots [tex]r=2[/tex] and [tex]r=1[/tex]. Then the characteristic solution is

[tex]\boxed{y = C_1 e^{2x} + C_2 e^x}[/tex]

By substituting [tex]z = y'[/tex] and [tex]z' = y''[/tex], the ODE transforms to

[tex]\dfrac{dz}{dx} - 3z + 2y = 0[/tex]

so we have the system of ODEs

[tex]\begin{cases} z' = 3z - 2y \\ y' = z \end{cases}[/tex]

In matrix form,

[tex]\dfrac d{dx} \begin{bmatrix} z \\ y \end{bmatrix} = \begin{bmatrix} 3 & -2 \\ 1 & 0 \end{bmatrix} \begin{bmatrix} z \\ y \end{bmatrix}[/tex]

Compute the eigenvalues of the coefficient matrix.

[tex]\begin{vmatrix} 3 - \lambda & -2 \\ 1 & -\lambda \end{vmatrix} = \lambda^2 - 3\lambda + 2 = (\lambda - 2) (\lambda - 1) = 0 \\\\ \implies \lambda = 2 \text{ or } \lambda = 1[/tex]

Compute the corresponding eigenvectors.

[tex]\lambda = 2 \implies \begin{bmatrix} 1 & -2 \\ 1 & -2 \end{bmatrix} \vec v = \vec 0 \implies \vec v = \begin{bmatrix}2 \\ 1\end{bmatrix}[/tex]

[tex]\lambda = 1 \implies \begin{bmatrix}2 & -2 \\ 1 & -1 \end{bmatrix} \vec v = \vec 0 \implies \vec v = \begin{bmatrix}1 \\ 1 \end{bmatrix}[/tex]

Then the characteristic solution to the system is

[tex]\begin{bmatrix} z \\ y \end{bmatrix} = C_1 e^{2x} \begin{bmatrix} 2 \\ 1 \end{bmatrix} + C_2 e^x \begin{bmatrix}1 \\ 1 \end{bmatrix}[/tex]

but we only want the second component,

[tex]\boxed{y = C_1 e^{2x} + C_2 e^x}[/tex]

You also mention "initial value problem" but it's unclear what the initial values are. It looks like you might have meant [tex]y(0)=6[/tex] and [tex]y'(0) = -5[/tex], in which case

[tex]y(0) = C_1 + C_2 = 6[/tex]

[tex]y'(0) = 2C_1 + C_2 = -5[/tex]

By elimination,

[tex](C_1 + C_2) - (2C_1 + C_2) = 6 - (-5) \implies -C_1 = 11 \\\\ \implies C_1 = -11 \text{ and } C_2 = 17[/tex]

and so the particular solution is

[tex]y = -11 e^{2x} + 17 e^x[/tex]

You did write d2y/dx2=-5, though, so you also could have meant [tex]y''(0) = -5[/tex], n which case

[tex]y(0) = C_1 + C_2 = 6[/tex]

[tex]y''(0) = 4C_1 + C_2 = -5[/tex]

[tex]\!\!\implies (C_1 + C_2) - (4C_1 + C_2) = 6 - (-5) \implies -3C_1 = 11\\\\ \implies C_1 = -\dfrac{11}3 \text{ and } C_2 = \dfrac{29}3[/tex]

Take your pick.

ACCESS MORE